COVID-19 pandemic - Social isolation, socio-emotional repercussions and mental health effects - Tinoco, Denise Lima; Istoe, Rosalee Santos Crespo; Silva, Rodrigo Lima Gonçalves da; Freitas, Salvador de Souza (Seven Editora, 2023)
It is known that the COVID-19 pandemic has affected several sectors, several individuals, in a potentiating way, including the elderly, who have been the focus of worrying news, victims of this virus, because they are part of the risk zone, because of their comorbidities involved. In this work, the main object of study is  to investigate the impact of social isolation among Brazilians during the COVID-19 pandemic period. To this end, we discuss the repercussions on socio-emotional feelings and the lifting of the effects of the COVID-19 pandemic on mental health. The study was qualitative, based on an exploratory qualitative theoretical perspective. Initially, we had the literature review, bringing authors on the theme presented here. The results showed that social isolation during the COVID-19 pandemic has aggravated problems that affect people's mental health, such as anxiety, depression, insecurity, insomnia. It is concluded, therefore, that the subjects deserve attention, even after the end of isolation, since the damages are real. DOI:https://doi.org/10.56238/emerrelcovid19-061